Potassium Solubilizing Microorganisms for Sustainable Agriculture 2016
DOI: 10.1007/978-81-322-2776-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Fungi: Role in the Solubilization of Potassium

Abstract: Mycorrhizae have been key living microorganisms in the plant colonization of terrestrial environments. The crucial roles of mycorrhizae are to provide plant nutrition and stress resistance for plant growth and development. Potassium (K + ) shows important functions in different metabolic processes and physiological functions and is the third crucial component of most crop fertilizers (after nitrogen and phosphorus). This chapter discusses the current state of knowledge about the role of mycorrhizal symbiosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(12 citation statements)
references
References 181 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…This increase could be explained as follows: (i) the AMF released metabolites that promoted rhizosphere activity (Azcón-Aguilar and Barea 2015), or (ii) the AMF secreted phosphatases that subsequently increased the total pool of these enzymes in the rhizosphere soil (Liu et al 2013;Sato et al 2015). Moreover, F. mosseae inoculation also increased the labile pool of K and the shoot K concentration, as observed previously by Meena et al (2014) and Dominguez-Nunez et al (2016).…”
Section: Impact Of Cadophora Sp and F Mosseae Inoculation On Soil Ementioning
confidence: 55%
“…This increase could be explained as follows: (i) the AMF released metabolites that promoted rhizosphere activity (Azcón-Aguilar and Barea 2015), or (ii) the AMF secreted phosphatases that subsequently increased the total pool of these enzymes in the rhizosphere soil (Liu et al 2013;Sato et al 2015). Moreover, F. mosseae inoculation also increased the labile pool of K and the shoot K concentration, as observed previously by Meena et al (2014) and Dominguez-Nunez et al (2016).…”
Section: Impact Of Cadophora Sp and F Mosseae Inoculation On Soil Ementioning
confidence: 55%
“…On the other hand, the increase of P in plants by association with mycorrhizal fungi is well documented in the literature (Walder et al, 2015); more than 90% of the P that is supplied to plants occurs by symbiosis with mycorrhizae (van der Heijden et al al., 2008). In the case of K, several studies have demonstrated that mycorrhizal symbiosis is able to participate in the solubilization of K and therefore increase the cation's uptake by plants (Dominguez‐Nuñez et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms have many mechanisms to solubilize K from a mineral source. Researchers have suggested that this solubilization might be either due to the excretion of protons, H+ or CO 2 and organic acids, causing acidification of the external medium, or to the excretion of chelating substances (such as siderophores) that form stable complexes with potassium adsorbents (aluminum, iron and calcium) [ 57 , 60 , 61 , 62 , 63 ]. In this research, the pH of the growth medium of all strains in AMM broth with orthoclase was between 7.2 and 6.2 at day 1 and stabilized afterwards in most cases at approximately pH 6.2, except for the AI and CYM strains ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%